Stem Cells From Human Exfoliated Deciduous Teeth Alleviate Liver Cirrhosis via Inhibition of Gasdermin D-Executed Hepatocyte Pyroptosis - Chen, Peng; Zhou, Yi-kun; Han, Chun-shan; Chen, Liu-jing; Wang, Yi-ming; Zhuang, Zi-meng; Lin, Shuai; Zhou, Yan-heng; Jiang, Jiu-hui; Yang, Rui-li (Frontiers in Immunology, 2022)
Liver cirrhosis represents a type of end-stage liver disease with few effective therapies, which was characterized by damaged functional liver tissue due to long-term inflammation. Gasdermin D (GSDMD)-executed programmed necrosis is reported to be involved in inflammation. However, the role of GSDMD in liver cirrhosis remains unclear. In this study, we used a CCl4-induced cirrhosis model and found stem cells from human exfoliated deciduous teeth (SHED) infusion showed profound therapeutic effects for liver cirrhosis. Mechanistically, NLRP3 inflammasome-activated GSDMD and its pyroptosis were upregulated in liver cirrhosis, while SHED infusion could suppress the expression of GSDMD and Caspase-1, resulting in reduced hepatocyte pyroptosis and inflammatory cytokine IL-1β release. Consistently, SHED could inhibit the elevated expression of NLRP3, GSDMD and Caspase-1 induced by CCl4 treatment in vitro co-culture system, which was mediated by decreasing reactive oxygen species (ROS) generation. Moreover, the pyroptosis inhibitor disulfiram showed similar therapeutic effects for liver cirrhosis as SHED. In conclusion, SHED alleviates CCl4-induced liver cirrhosis via inhibition of hepatocytes pyroptosis. Our findings could provide a potential treatment strategy and novel target for liver cirrhosis.